POLA PERJALANAN DI DESA KUTA MANDALIKA SEBAGAI PENGEMBANGAN DESTINASI BERKELANJUTAN - damayanti, miswa sari (Tourism, Hospitality And Culture Insights Journal, 2024)
This research aims to determine the travel pattern model and tourism potential of Kuta Mandalika Village. By using the 5A identification method, we can develop travel patterns in Kuta Mandalika Village as a Super Priority Destination. The research method used in this final project is descriptive qualitative, using interview, observation and documentation data collection techniques. The data that has been collected is then analyzed using data reduction techniques, then presenting the data until finally drawing conclusions from the data. In the results of this final project research, it can be seen that the potential of Kuta Mandalika Village in terms of the 5A components, namely accommodation, accessibility, attractions, amenities and activities, is suitable for visits by domestic and foreign tourists. So the STOPOVER travel pattern model was created.